1995
DOI: 10.1089/aid.1995.11.1321
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Activation of the Human Immunodeficiency Virus Long Terminal Repeat by CD8+T Cells Is Not Lentivirus Specific

Abstract: CD8+ T lymphocytes of HIV-1-infected individuals can efficiently suppress HIV-1 replication in CD4+ T lymphocytes. To elucidate the molecular events underlying this suppression, we have used the HIV-1 LTR directing the chloramphenicol acetyltransferase gene (CAT) in transient transfection assays using human Jurkat T cells. In addition to supernatants of patient CD8+ T lymphocytes (CD4+ > 350/microliters), supernatant of a T cell clone derived by Herpesvirus saimiri (HVS)-mediated transformation of CD8+ T lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 38 publications
4
47
0
Order By: Relevance
“…CD8 + T cells from asymptomatic HIV-1 infected individuals could inhibit both basal and Tat mediated transcription and other work further substantiated these findings [19,20]. Importantly, these affects on viral gene expression were also observed and confirmed using a primary lymphocyte culture in an ongoing cycle of viral replication where potent suppression of CXCR4-tropic viruses was shown not to involve entry or reverse transcription [21].…”
Section: Introductionmentioning
confidence: 72%
“…CD8 + T cells from asymptomatic HIV-1 infected individuals could inhibit both basal and Tat mediated transcription and other work further substantiated these findings [19,20]. Importantly, these affects on viral gene expression were also observed and confirmed using a primary lymphocyte culture in an ongoing cycle of viral replication where potent suppression of CXCR4-tropic viruses was shown not to involve entry or reverse transcription [21].…”
Section: Introductionmentioning
confidence: 72%
“…We previously reported that while CD8 þ T cell supernatants suppress HIV-1 LTR-mediated gene expression in Jurkat T cells [18,19], an opposite effect was observed on gene expression in monocytic cells [22]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition to inhibition of HIV-1 replication in CD4 þ T cells and T cell lines, CD8 þ T cells mediate inhibition of LTR-directed gene expression in T cell lines [17][18][19][20][21]. We previously reported on the opposite effects of CD8 þ T cells on gene expression in T cells versus monocytic cells [22].…”
Section: Introductionmentioning
confidence: 99%
“…It does not directly inactivate HIV but blocks virus transcription (12,13,29). The amount of CAF in CD8 ϩ cell culture fluids is low (e.g., 4 units͞ml in which 1 unit is 50% inhibition of HIV replication), and thus it is difficult to isolate CAF from the serum-or protein-containing media in which CD8 ϩ cells must be grown (4).…”
Section: Discussionmentioning
confidence: 99%
“…CNAR appears to be mediated by the secretion of a soluble CD8 ϩ cell antiviral factor (CAF), which, as observed with CNAR, blocks HIV transcription (8,12,13). CAF in culture fluids can be measured by culturing acutely infected CD4 ϩ cells in the continual presence of the CD8 ϩ cell supernatant.…”
mentioning
confidence: 99%